2013
DOI: 10.1136/acupmed-2013-010363
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for Vascular Mild Cognitive Impairment: A Systematic Review of Randomised Controlled Trials

Abstract: Background Vascular mild cognitive impairment (VMCI) is the most common type of vascular cognitive impairment induced by cerebrovascular disease. No effective medicines are currently available for VMCI. Objective To assess the effectiveness and safety of acupuncture for VMCI. Methods Seven electronic databases were searched for randomised controlled trials which investigated the effects of acupuncture compared with no treatment, placebo or conventional therapies on cognitive function or other clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 1 publication
1
51
0
Order By: Relevance
“…16 A number of studies have shown that acupuncture may improve intelligence and memory, and stimulate consciousness. 17 Some reports have also confirmed that acupuncture can inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 A number of studies have shown that acupuncture may improve intelligence and memory, and stimulate consciousness. 17 Some reports have also confirmed that acupuncture can inhibit apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the pharmacological therapies, acupuncture has also been explored to treat VCI [ 14 ]. A recent systematic meta-analysis including 691 participants pooled from 12 randomized controlled trials has shown that combination therapy of acupuncture plus other conventional therapy improved mini-mental state examination (MMSE) score significantly in patients with vascular MCI [ 14 ]. However, all the included clinical trials appear to have low quality in methodology and high risk of bias [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have suggested that acupuncture might be beneficial in MCI. 9 Traditional Chinese acupuncture has been practised for more than 3000 years. Recent research has reported that acupuncture may be an effective adjunctive therapy for neurological diseases, including stroke, 10 Parkinson's disease, 11 vascular dementia, 12 and AD.…”
Section: Introductionmentioning
confidence: 99%